The Impact Of Time Management On Employee Performance Field Study On The General Company For Cotton Filaments In Lattakia - Nasser, Feras Adnan (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The Aim Of The Research Was To Determine The Impact Of Time Management On The Performance Of Employees In The The General Cotton Filaments Company In Lattakia Province,And To Achieve This Goal The Researcher Conducted A Field Study On This Company, And The Study Community Consisted Of All The Employees In The Company Who Number (2423) Employees, And A Sample Was Drawn Simple Random From The Research Community. And The Total Number Of The Sample Ofemployeesis 332 Employees, Distributed Between (27) Administrators (88) Technicians, And (192) Production Workers And (25) Service Employees. Using Appropriate Distribution. The Research Reached A Set Of Results, The Most Important Of Which Are:There Is A High Impact Of The Two Elements Of Time Management (Time Orientation, Time Control) Onraising The Level Of Employeeperformance.. The Study Also Found That There Is A Statistically Significant Relationship Between Time Management And Worker Performance, While There Are No Statistically Significant Differences Significant Between Employees About The Effectiveness Of Time Management Performance (Planning, Organizing, Directing, Control). In The Company Due To The Level Of Nature Of The Work.The Study Concluded With A Set Of Recommendations, The Most Important Of Which Are: Holding Training Courses For Employees In The Field Of Time Management, The Necessity For Employees To Use Time Management Tools, And Paying Attention To The Morale Of Employees. هدف البحث إلى تحديد أثر إدارة الوقت في مستوى أداء العاملين في الشركة العامة للخيوط القطنية باللاذقية. ولتحقيق هذا الهدف أجرى الباحث دراسة ميدانية على هذه الشركة، وتكون مجتمع الدراسة من جميع العاملين في الشركة البالغ (2423) عامل، وقد تم سحب عينة عشوائية بسيطة من مجتمع البحث، وبلغ مجموع أفراد العينة من العاملين (332)عاملاً، يتوزعون بين ( 27) إدارياً و(88) فنياً و (192) عامل إنتاج و (25) عامل خدمي. مستخدماً التوزيع المتناسب. توصل البحث إلى مجموعة من النتائج أهمها: أن هناك أثراً مرتفعاً لعنصري إدارة الوقت (لتخطيط الوقت، وتنظيم الوقت)، وأثر متوسط لعنصري إدارة الوقت ( توجيه الوقت، والرقابة على الوقت) على رفع مستوى أداء العاملين، وأن مستوى أداء العاملين يتأثر بعمل نظام الحوافز المرتبط بوقت الانجاز على رفع مستوى أداء العاملين، وتوصلت الدراسة أيضاً إلى وجود علاقة ذات دلالة إحصائية بين إدارة الوقت وأداء العاملين، في حين عدم وجود فروق ذات دلالة إحصائية بين العاملين حول مدى فعالية أداء إدارة الوقت (تخطيط،تنظيم،توجيه،رقابة) في الشركة تعزى لمستوى طبيعة العمل. وخلصت الدراسة إلى مجموعة من التوصيات أهمها: عقد دورات تدريبية للموظفين في مجال إدارة الوقت، وضرورة قيام العاملين باستخدام أدوات إدارة الوقت، والاهتمام بالروح المعنوية للعاملين.